The secret kingdom / 1. - Nimmo, Jenny (Scholastic Press, 2011)
Timoken and his sister, Zobayda, under the protection of a forest jinni but pursued by evil virideed, straddle the world of men and the world of enchantments, seeking a home while remaining young by drinking a potion called Alixir.